Experimental observations and modelling of radiation asymmetries during N2 seeding in LHD. (March 2021) - Peterson, B.J.; Kawamura, G.; van de Giessen, P.L.; Mukai, K.; Tanaka, H.; Sano, R.; Pandya, S.N.; Dai, S.Y.; Masuzaki, S.; Akiyama, T.; Kobayashi, M.; Goto, M.; et al.
Abstract: N2 gas has been seeded in the Large Helical Device (LHD) to reduce the divertor heat load through enhanced radiation. Radiation is observed by two imaging bolometers, viewing the same poloidal cross-section from top and bottom ports, at a location which is 36° toroidally removed from the N2 gas puff nozzle located at the bottom of the machine. During N2 seeding, these measurements both confirm that additional radiation from the outboard side is coming exclusively from the top of the cross-section, indicating up/down asymmetry, which is also reproduced by modelling with EMC3-EIRENE using a half torus model. In addition, a toroidally localized, magnetic field direction-dependent radiation enhancement is observed with N2 seeding, but is not reproducible by the model.